2024
DOI: 10.1615/critrevtherdrugcarriersyst.2023039877
|View full text |Cite
|
Sign up to set email alerts
|

Stability Challenges of Amorphous Solid Dispersions of Drugs: A Critical Review on Mechanistic Aspects

Abstract: The most common drawback of the existing and novel drug molecules is their low bioavailability because of their low solubility. One of the most important approaches to enhance the bioavailability in the enteral route for poorly hydrophilic molecules is amorphous solid dispersion (ASD). The solubility of compounds in amorphous form is comparatively high because of the availability of free energy produced during formulation. This free energy results in the change of crystalline nature of the prepared ASD to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 176 publications
0
5
0
Order By: Relevance
“…Therefore, the experimental findings suggested that elevating the agitation speed to 500 rpm resulted in the formation of a more physically stable amorphous solid in the present investigation. 2 represents the goodness of fit, while the Q 2 represents the goodness of prediction). The crystalline Form A was used as a reference sample; the feeding rate was fixed at 5 mL/min, and the aging time was fixed at 10 min.…”
Section: Pdf Analysis and Pca Of Pxrd Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the experimental findings suggested that elevating the agitation speed to 500 rpm resulted in the formation of a more physically stable amorphous solid in the present investigation. 2 represents the goodness of fit, while the Q 2 represents the goodness of prediction). The crystalline Form A was used as a reference sample; the feeding rate was fixed at 5 mL/min, and the aging time was fixed at 10 min.…”
Section: Pdf Analysis and Pca Of Pxrd Datamentioning
confidence: 99%
“…These thermal effects can significantly impact the physical stability of amorphous solids. Consequently, the DSC analysis 2 represents the goodness of fit, while the Q 2 represents the goodness of prediction). The crystalline Form A was used as a reference sample; the feeding rate was fixed at 5 mL/min, and the aging time was fixed at 10 min.…”
Section: Rc Analysis Of Dsc Datamentioning
confidence: 99%
See 3 more Smart Citations